New technologies for the intervention of stuttering: a review - Fernández-Martín, María; Calet, Nuria; González, José A. (Revista de Investigación en Logopedia, 2016)
The aim of this project was to analyse the most recent studies on the treatment of speech disfluencies through new technologies. The research has been performed through international (PubMed and Scopus) and national (Dialnet) databases of studies that use new technologies in the intervention of disfluency, published from 2000 to 2015. In general, it appears that the purpose of these programs is to reduce the percentage of stuttering through user-friendly devices. The methodology used is very diverse, although the studies have common features: the severity of stuttering was assessed prior to intervention to ensure that it decreased thanks to programs, as well as the analyses were performed pre and post treatment for all of them. In conclusion, positive results are obtained with the use of these programs, although they are not generalizable to the rest of the population with disfluencies. The use of devices on stutter may be beneficial for some people with speech disfluencies, even though studies with larger populations are needed to ensure its effectiveness in all cases.
Keywords: Feedback alteration; Intervention; New technologies; Speech disfluency; Stuttering.